(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Temple culture has a long history in West Bengal. There is more than one and a half thousand-year-old temples scattered all over Bengal, of which only a few exist today. The design of Indian temples followed the construction of temples in Bengal, so this was an ongoing aspect of Indian temple culture. Numerous witnesses to Bengal’s ancient history can be found in these temples